ANTIBIOTIC PROPERTIES FOR S ENTERITIDIS IN A AEGYPTI - VARELA, GERARDO; REBELO PEREZ, RODOLFO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1942)
S enteritidis transmitted to A aegypti by feeding them upon infected rats were destroyed within 1 hr after entry into the alimentary tract of the mosquito The bacteria persist in the digestive tract for 6 days when A aegypti is infected with honey co
REV SOC MEX HIST NAT
Keywords: ANTIBIOTIC PROPERTIES, S ENTERITIDIS, AEGYPTI; CIENCIAS DE LA VIDA; BIOLOGIA DE LOS INSECTOS (ENTOMOLOGIA)